Improving LiFe0.4Mn0.6PO4 Nanoplate Performance by a Dual Modification Strategy toward the Practical Application of Li-Ion Batteries - Mingfeng Tan; Helei Wei; Qi Li; Zhipeng Yu; Qiang Zhang; Mingzhi Lin; Bo Lin (Batteries, 2024)
A novel composite consisting of fluorine-doped carbon and graphene double-coated LiMn0.6Fe0.4PO4 (LMFP) nanorods was synthesized via a facile low-temperature solvothermal method that employs a hybrid glucose and polyvinylidene fluoride as carbon and fluorine sources. As revealed by physicochemical characterization, F-doped carbon coating and graphene form a ‘point-to-surface’ conductive network, facilitating rapid electron transport and mitigating electrochemical polarization. Furthermore, the uniform thickness of the F-doped carbon coating alters the growth of nanoparticles and prevents direct contact between the material and the electrolyte, thereby enhancing structural stability. The strongly electronegative F− can inhibit the structural changes in LMFP during charge/discharge, thus reducing the Jahn–Teller effect of Mn3+. The distinctive architecture of the LMFP/C-F/G cathode material exhibits excellent electrochemical properties, exhibiting an initial discharge capacity of 163.1 mAh g−1 at 0.1 C and a constant Coulombic efficiency of 99.7% over 100 cycles. Notably, the LMFP/C-F/G cathode material achieves an impressive energy density of 607.6 Wh kg−1, surpassing that of commercial counterparts. Moreover, it delivers a reversible capacity of 90.3 mAh g−1 at a high current rate of 5 C. The high-capacity capability and energy density of the prepared materials give them great potential for use in next-generation lithium-ion batteries.